ANALISIS KUALITAS AIR DISEKITAR SITUS TPA SUMOMPO KOTA MANADO - Maria Insiana Su; Verry R. Ch. Warouw; Karamoy Lientje Theffie (COCOS, 2017)
ABSTRACTThe research was conducted around the site of the final processing site (TPA) of Sumompo Manado municipal waste, with the aim to analyze the water quality around the Sumompo TPA site. Benefits of research that can provide information to the community and local government about the quality of water around the Site TPA waste, including: Groundwater quality, surface water and leachate. The research was conducted using survey method and the data was analyzed by desktritif, tabelaris and garif. TPA sampling point using GPS (Global Position System), and determination of sampling point by purposive sampling technique. The parameters observed through physical, chemical and microbiological aspects. The results showed that the total coliform parameters for springs, wells and boreholes respectively were 17, 27 and 2 APM / 100ml, which means exceeding the quality standard of water in accordance with Permenkes N0. 492 of 2010. The quality of leachate river water with BOD parameters 110 mg / l, COD 323 mg / l, TDS 1830 mg / l, and Nitrate 13.10 mg / l which has exceeded the quality standard according to class II based on PP. No. 82 in 2001. Leachate quality of inlet leachate and leachate drainage with COD, TDS and Nitrate parameters were 898 mg / l, 4130 mg / l and 111.01 mg / l and 334 mg / l, 5170 mg / l, respectively, L and 144.6 mg / l exceeding the leachate effluent quality standard. In accordance with the Standard Operating Standards Manual (NSPM) 2006.Keywords: Sumompo TPA, Water Quality